Staged extubation to manage the airway after operations on the head and neck. Issue 9 (November 2016) - Twohig, Eoin M.; Leader, Ross; Shaw, Richard J.; Charters, Peter
Abstract: Management of the airway after operations on the head and neck is potentially problematic. We describe leaving a guidewire in the trachea after successful extubation in two patients, to make reintubation easier if the airway was later compromised.